A Protestant theology of passion: Korean Minjung theology revisited - Küster, Volker (Studies in systematic theology, 2010)
Foreword / by David Kwang-Sun Suh -- Writing from this place -- Theology in context -- People as the subjects of history -- Re-constructing Korean identity the Minjung culture movement -- Theology and biography theological identity re-constructed -- Jesus and the Minjung Ahn Byung-Mu (1922-1996) -- A confluence of two traditions Shu Nam-Dong (1918-1984) -- Fools for Christ's sake Hyun Young-Hak (1921-2004) -- Theology as a social biography of the Minjung Kim Yong-Bock (1938) -- A plea for a survival-liberation centered syncretism Chung Hyun-Kyung (1956) -- Contextual challenges Minjung theology in intercultural perspective -- Contextual transformations Minjung theology yesterday and today -- Epilogue: Contextual theologies as open systems